Effect of Temperature on the Mechanical Properties of Carbon Composites - Ali Anvari (Journal of Engineering)
The purpose of this research is to investigate and analyze the effect of temperature on the mechanical properties of carbon composites, aluminum foam, and carbon nanotube reinforced aluminum foam. For this analysis, fatigue behavior of aluminum foam has been discussed, and interlaminar shear stress between single-walled carbon nanotube reinforced aluminum foam and multiwalled carbon nanotube reinforced aluminum foam has been compared. The comparison has shown that the interlaminar shear stress within the interface of single-walled carbon nanotube and aluminum foam is higher than that within the interface of multiwalled carbon nanotube and aluminum foam. Hence, the probability of stress concentration and crack initiation within the interface of single-walled carbon nanotube and aluminum foam is higher than that within the interface of multiwalled carbon nanotube and aluminum foam. Furthermore, thermal fatigue lives of different single-walled carbon nanotube reinforced matrix nanocomposites have been evaluated. Additionally, interaction between carbon and molten aluminum has been analyzed. Finally, a new relation for the thermal interlaminar shear stress intensity factor to predict the crack initiation sites on fiber/matrix interface has been introduced.